(untitled) (Research, Society and Development, 2021)
Recently, with the advent of Orofacial Harmonization, there has been a great demand of people, mainly women, exhibiting in their social networks, or in the media in general, the aesthetic and rejuvenating treatments performed. Among the most chosen regions, the lips seem to be one of the most sought after. Thus, this integrative review aims to investigate the main complications related to filling the lips with Hyaluronic Acid (HA), for aesthetic purposes, and how they were treated. Articles from the last 10 years were selected, using the databases of the Virtual Health Library - BVS and PubMed, obtaining a sample of 107 publications of clinical cases that after applying the inclusion and exclusion criteria resulted in 08 articles that were included in this integrative review. After analyzing the articles included in the review, the results of the studies indicated that among the main complications are nodules or granulomas, understood as foreign bodies. In these cases, biopsy, most of the times excisional, was presented as a treatment procedure.